The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1021/acsami.7b09161
|View full text |Cite
|
Sign up to set email alerts
|

WO3 and W Thermal Atomic Layer Etching Using “Conversion-Fluorination” and “Oxidation-Conversion-Fluorination” Mechanisms

Abstract: The thermal atomic layer etching (ALE) of WO and W was demonstrated with new "conversion-fluorination" and "oxidation-conversion-fluorination" etching mechanisms. Both of these mechanisms are based on sequential, self-limiting reactions. WO ALE was achieved by a "conversion-fluorination" mechanism using an AB exposure sequence with boron trichloride (BCl) and hydrogen fluoride (HF). BCl converts the WO surface to a BO layer while forming volatile WOCl products. Subsequently, HF spontaneously etches the BO laye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
117
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 72 publications
(126 citation statements)
references
References 67 publications
(127 reference statements)
3
117
0
Order By: Relevance
“…For the oxygen ion beam, 300 W of RF power was applied to the ICP source at 1 mTorr of O 2 while applying + 30– + 100 V to the first grid, −100 V to the second grid, and 0 V (grounded) to the third grid. The formation of WO x was estimated by the increased W thickness after the oxygen ion beam exposure using a surface profilometer because, during the oxygen exposure, the thickness of W is increased by the formation of WO x . (In fact, because it is difficult to measure the thickness of a self‐limiting oxidation step of a few angstroms with a profilometer, the oxidation time was increased until the oxide thickness can be measured by the profilometer and the data were extrapolated to the lower oxidation time.)…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…For the oxygen ion beam, 300 W of RF power was applied to the ICP source at 1 mTorr of O 2 while applying + 30– + 100 V to the first grid, −100 V to the second grid, and 0 V (grounded) to the third grid. The formation of WO x was estimated by the increased W thickness after the oxygen ion beam exposure using a surface profilometer because, during the oxygen exposure, the thickness of W is increased by the formation of WO x . (In fact, because it is difficult to measure the thickness of a self‐limiting oxidation step of a few angstroms with a profilometer, the oxidation time was increased until the oxide thickness can be measured by the profilometer and the data were extrapolated to the lower oxidation time.)…”
Section: Resultsmentioning
confidence: 99%
“…The formation of WO x was estimated by the increased W thickness after the oxygen ion beam exposure using a surface profilometer because, during the oxygen exposure, the thickness of W is increased by the formation of WO x . [33] (In fact, because it is difficult to measure the thickness of a self-limiting oxidation step of a few angstroms with a profilometer, the oxidation time was increased until the oxide thickness can be measured by the profilometer and the data were extrapolated to the lower oxidation time.) Figure 2(b) shows the changes in WO x thickness on the W surface measured by the surface profilometer with increasing first grid voltage from + 30 to + 100 V and O x + ion exposure time from 0 to 60 s. The first grid voltage is directly related to the oxygen ion energy from the ion source and the ion energy distributions measured by a retarding grid ion energy analyzer for the different first grid voltages are shown in Figure S1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, progress toward the isotropic thermal ALE of metallic W has been reported by the groups of George and Parsons. The work reported by George et al ( 13 ) has shown the quasi-ALE of metallic W via a conversion etch mechanism utilizing ozone (O 3 ), BCl 3 , and anhydrous HF vapor. In this system, ozone was used to oxidize the W surface to WO 3 in a diffusion-limited process, which then reacts with BCl 3 to generate a volatile etch product in the form of WO x Cl y while tandemly generating a B 2 O 3 surface layer, which is then susceptible to self-limiting etch by HF.…”
Section: Introductionmentioning
confidence: 99%